Usage of Library Collection, Services & Assistance Among Ophthalmologists - An Opinion Survey - Govindarajan, R.; Dhanavandan, S. (International Journal of Knowledge Content Development & Technology, 2020)
Accurate and reliable Information improves decision making, reduces costs, and saves time. The ophthalmic Libraries supply quality ophthalmic information to the ophthalmologists to serve the patients in a better way and stimulate the growth of ophthalmic field. This paper aims to study the usage of library collection, services and assistance among the Ophthalmologists – Eye Doctors in India. A survey method is used to obtain the ophthalmologists' usage of library collection, services and assistance. Through convenient sampling method, a structured questionnaire is circulated to the ophthalmologists in India and 633 ophthalmologists are responded. Among the 633 ophthalmologist, 82.15% of the ophthalmologists use the library collection - book. 73.46% of the ophthalmologists use the online data / journals. 89.73% of the ophthalmologists seek assistance to locate books/articles/documents. There exist a significant difference between the ophthalmologists use of Library Service and gender (p value 0.001**). There exist a significant difference between the ophthalmologists use of Library Assistance / help and designation category (p value 0.000**). There exist a significant difference between the ophthalmologists use of Library Assistance / help and working experience (p value 0.017**). There exist a significant difference between Library Services (p value 0.009**), Library Assistance / help (p value 0.000**) and institution type. The study results will help the ophthalmic libraries to serve the user better. URL: http://ijkcdt.net/xml/24238/24238.pdf